Coordination Artifacts: A Unifying Abstraction for Engineering Environment-Mediated Coordination in MAS - Ricci, A.; Viroli, M. (Informatica)
Coordination Artifacts: A Unifying Abstraction for Engineering Environment-Mediated Coordination in MAS